دراسة مقارنة بين الأوكسي توسين والميزوبروستول في الوقاية من نزوف الخلاص - محمد, عدنان; سلوم, ديما (Latakia University Journal -Medical Sciences Series, 2014)
اشتمل هذا البحث على 150 سيدة حامل بعمر حملي 36 أسبوعاً أو أكثر مقبولة في قسم التوليد وأمراض النساء في مشفى الأسد الجامعي باللاذقية من أجل الولادة المهبلية الطبيعية خلال فترة الدراسة ( 1/1/2012 حتى 1/7/2013 م ). حيث تم استبعاد المريضات اللواتي ولدن بقيصرية، المريضات مع مشيمة منزاحة أو انفكاك مشيمة، هيموغلوبين <9 غ%، ارتفاع ضغط حملي أو ما قبل إرجاج- إرجاج، الحمل المتعدد، اضطرابات تخثر الدم، قصة إيجابية سابقة لنزوف الخلاصPPH (Post Partum Haemorrhage)، النزف الزائد أو أي اختلاط طبي آخر. تم توزيع المريضات عشوائياً إلى ثلاث مجموعات: ( 1: مجموعة تمسيد الرحم /2 : 10وحدات أوكسي توسين ضمن 500 مل سيروم سكري تسريب وريدي بعد ولادة الكتف الأمامية ̎ مجموعة المقارنة ̎ / 3: 3 مضغوطات ميزوبروستول شرجي عيار 200مكغ̎ مجموعة الدراسة̎). حيث لم تكن هناك اختلافات إحصائية بين المجموعات الثلاث من حيث الصفات القاعدية الأساسية. شوهدت خسارة الدم المقدرة ≥500 مل لدى 18%(50\9) من مريضات المجموعة الأولى و 6%(50\3) من مريضات المجموعة الثانية و 8%(50\4) من مريضات المجموعة الثالثة. الاستخدام الروتيني ل 600 مكغ ميزوبروستول شرجي كان فعالاً في الإنقاص من خسارة الدم بعد الولادة (RR 0.44 ; CI 0.32 – 1.53)، لكنّه لم يكن بنفس فعالية الأوكسي توسين(RR 1.33 ; CI 0.4 – 3.39) وعلى الرغم من وجود هذه الاختلافات بين الأوكسي توسين والميزوبروستول إلاَّ أنَّها لم تكن ذات أهمية إحصائية (لم تكن هناك اختلافات ذات أهمية إحصائية فيما يتعلق بطول المرحلة الثالثة للمخاض، خسارة الدم المقدرة، التغيرات في تراكيز الهيموغلوبين والهيماتوكريت، الحاجة لمقبضات رحم إضافية، الحاجة لاستخلاص مشيمة يدوي، نقل دم....). هذه الجرعة من الميزوبروستول وطريقة الإعطاء كانت محتملة بشكل جيد، والآثار الجانبية الاعتيادية كالعرواءات والحمى كانت عابرة تراجعت من تلقاء نفسها ولم تكن مهددة للحياة. ولأنَّ الـPPH هو السبب المباشر الأكثر أهمية للوفيات الوالدية ولأن معظم هذه الوفيات تحدث في الأماكن منخفضة الموارد، لذلك فإن الميزوبروستول قد يقدم عدة منافع تفوق الأوكسي توسين في تلك الأماكن حيث يتواجد على شكل أقراص، متوافر عالمياً، ميسور التكلفة، لا يحتاج لشروط خاصة للتخزين ( ثابت في حرارة محيط الغرفة، لا يتطلب شروط خاصة للنقل، وعمر تخزينه يستمر عدة سنوات). إنّه أيضاً لا يحتاج أيّ مهارات أو معدّات أو تسهيلات خاصة لاستخدامه. ممّا يمكنه من أن يملأ الثغرات الموجودة في خدمات الولادة في الحالات التي لا تتمكن منها المرأة أو مقدّمي الرعاية من الحصول على الأوكسي توسين. This search included 150 pregnant women who had gestational age of 36 weeks or more, and had been admitted to the Department of Obstetrics and Gynecology at Al – Assad University Hospital in Lattakia for the spontaneous vaginal delivery during the study period ( 1\1\2012 to 1\7\ 2013). Exclusion criteria were patients undergoing cesarean section, patients with placenta previa, or abruptio placenta, patients with hemoglobin<9 gm%, pregnancy-induced hypertension or pre eclampsia–eclampsia, grand multiparty, coagulation abnormalities, positive history of PPH, expensive hemorrhage or other medical disorders. Patients were randomly divided into three groups: ( 1: uterine massage group, 2: 10 units oxytocin in 500 cc glucose 5% intravenously with delivery of the anterior sholder\ control group, 3: three 200µg rectal misoprostol tablets\study group). No significant differences were observed between the groups regarding baseline characteristics. There was blood loss of ≥500 ml occurred in 18% in the first group, 6% in the second group, 8% in the third group. Routine use of 600 µg of rectal misoprostol was effective in reducing blood loss after delivery ل gm%, pregnancyts with hemoglobin}ergoing cesarean section, patients with placenta pre and g (RR 0.44 ; CI 0.32 – 1.53), but not as effective as intravenous oxytocin (RR 1.33 ; CI 0.4 – 3.39). Although these were differences, they were not significant (No significant differences were observed between the control and study groups for the length of the third stage of labor, the estimated blood loss, the changes in Hb and Hct concentrations, need for additional uterotonics, manual removal of placenta, blood transfusion…..). This dose of misoprostol and route of administration were well tolerated, and usual side effects such as shivering and fever were transient, resolved on their own, and were not threatening. Because PPH is the most significant direct cause of maternal mortality and because most of these maternal mortality occurs in low resource countries, misoprostol offers several advantages over oxytocin in such settings. It is formulated as a tablet, widely available and affordable, and it does not need require special storage conditions (i.e. it is stable at ambient room temperature and does not require specific conditions for transfer and has a shelf-life of several years). It also does not require any special skills, equipment, or facilities for its use. So misoprostol can fill a service delivery gap in settings where women and providers are unable to access oxytocin.ل gm%, pregnancyts with hemoglobin}ergoing cesarean section, patients with placenta pre and g